Targeting IKKβ in Cancer: Challenges and Opportunities for the Therapeutic Utilisation of IKKβ Inhibitors - Jack A. Prescott; Simon J. Cook (Cells, 2018)
Deregulated NF-κB signalling is implicated in the pathogenesis of numerous human inflammatory disorders and malignancies. Consequently, the NF-κB pathway has attracted attention as an attractive therapeutic target for drug discovery. As the primary, druggable mediator of canonical NF-κB signalling the IKKβ protein kinase has been the historical focus of drug development pipelines. Thousands of compounds with activity against IKKβ have been characterised, with many demonstrating promising efficacy in pre-clinical models of cancer and inflammatory disease. However, severe on-target toxicities and other safety concerns associated with systemic IKKβ inhibition have thus far prevented the clinical approval of any IKKβ inhibitors. This review will discuss the potential reasons for the lack of clinical success of IKKβ inhibitors to date, the challenges associated with their therapeutic use, realistic opportunities for their future utilisation, and the alternative strategies to inhibit NF-κB signalling that may overcome some of the limitations associated with IKKβ inhibition.